2018
DOI: 10.3389/fpubh.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Facility-Based Maternal Death in Western Africa: A Systematic Review

Abstract: BackgroundFor exploring maternal death, supply and demand-side factors can be characterized by the three delays model developed by Thaddeus and Maine (1994). The model comprises delay in deciding to seek care (delay 1), delay in reaching the health facility (delay 2), and delay in receiving quality care once at the health facility (delay 3). Few studies have comprehensively dealt with the health systems delays that prevent the receipt of timely and appropriate obstetric care once a woman reaches a health facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Many women do not deliver in hospitals because of costs, education or the perception or accessibility of health services [4,[11][12][13][14][15][16]. Studies on the factors that affect maternal mortality extensively used the three delays model examining barriers on the demand side (phases 1 and 2 delay) and on the supply side (phase 3 delay) [17] to understand and intervene on the barriers to prevent maternal death [4,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Many women do not deliver in hospitals because of costs, education or the perception or accessibility of health services [4,[11][12][13][14][15][16]. Studies on the factors that affect maternal mortality extensively used the three delays model examining barriers on the demand side (phases 1 and 2 delay) and on the supply side (phase 3 delay) [17] to understand and intervene on the barriers to prevent maternal death [4,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey indicated that 62% of maternal deaths occurred at health facilities and an additional 21% among mothers who just returned home after delivering in a facility 26. Hence, reducing facility-based maternal deaths at birth by acting to improve quality of service delivery and extending women’s in-hospital stays is likely to bear an important impact on the country’s overall maternal mortality, considering Malawi’s situation with over 90% of women giving birth at a facility11 in the context of poor obstetric care quality 28 29. However, we cannot fully appraise the mortality reduction produced by the RBF4MNH in relation to other maternal care interventions due to the current lack of comparable studies.…”
Section: Discussionmentioning
confidence: 98%
“…The review showed that these QI programmes have focused on many factors that critically influence the quality of care. These factors are well described in the scientific literature 31–34. They mostly relate to human resources development and to weak referral mechanisms.…”
Section: Lessons Learntmentioning
confidence: 99%